Managing Peak Loads by Leasing Cloud Infrastructure Services from a Spot Market - Mattess, Michael; Vecchiola, Christian; Buyya, Rajkumar (2010 IEEE 12th International Conference on High Performance Computing and Communications, 2010)
Dedicated computing clusters are typically sized based on an expected average workload over a period of years, rather than on peak workloads, which might exist for relatively short times of weeks or months. Recent work has proposed temporarily adding capacity to dedicated clusters during peak periods, by purchasing additional resources from Infrastructure as a Service (IaaS) providers such as Amazon's EC2. In this paper, we consider the economics of purchasing such resources by taking advantage of new opportunities offered for renting virtual infrastructure such as the spot pricing model introduced by Amazon. Furthermore, we define different provisioning policies and investigate the use of spot instances compared to normal instances in terms of cost savings and total breach time of tasks in the queue.